The Study of Mooring Buoy Operability to Support Offloading Operation of Shuttle Tankers with Various Capacities - Mochammad Afif Zahiru Fajar; Eko Budi Djatmiko; Murdjito Murdjito (DRPM (Direktorat Riset dan Pengabdian kepada Masyarakat) ITS, 2020)
This study was conducted to analyse of the operability of mooring buoy initially designed for offloading operation of 35,000 DWT shuttle tankers enhanced to serve the offloading operations of shuttle tankers with 50,000 DWT, 75,000 DWT, and 111,000 DWT capacities. Operability is reviewed in term of mooring line tensions induced by each new variation of tanker capacity under environmental conditions of 1-year, 10-year, and 100-year recurrence. The governing criteria is that the safety factor should meet the appropriate limit as stated in the API RP2SK. Tension on the mooring line increases in parallel with the increasing of tanker capacity. For the case of 35,000 DWT and 50,000 DWT shuttle tankers the operation can be performed in all environmental conditions. For the case of 75,000 DWT shuttle tanker with full load and 67% DWT capacity can fully operate in all environmental conditions, but with 47% DWT capacity could not be operated in the 100-year environmental condition with significant wave height 3.31 m for the direction of inline-L1, inline-L2, and between line-L1&L4. For the case of 111,000 DWT shuttle tanker at all capacity conditions can fully operate in the 1-year environmental condition with significant wave height up to 1.48 m.